Flavour types used by youth and adult tobacco users in wave 2 of the Population Assessment of Tobacco and Health (PATH) Study 2014–2015. Issue 4 (21st September 2019) - Rose, Shyanika W; Johnson, Amanda L; Glasser, Allison M; Villanti, Andrea C; Ambrose, Bridget K; Conway, Kevin; Cummings, K. Michael; Stanton, Cassandra A.; Delnevo, Cristine; Wackowski, Olivia A; Edwards, Kathryn C; Feirman, Shari P; et al.
Abstract : Background: Most youth and young adult (YA) tobacco users use flavoured products; however, little is known about specific flavours used. Methods: We report flavour types among US tobacco users from the Population Assessment of Tobacco and Health Study, wave 2, 2014–2015. At wave 2, we examined (1) flavour use and type at past 30-day use; (2) new flavoured tobacco product use and type; (3) product-specific flavour patterns across youth (ages 12–17) (n=920), YA (18–24) (n=3726) and adult (25+) (n=10 346) past 30-day and new tobacco users and (4) concordance between self-coded and expert-coded brand flavour type among all adults (18+). Results: Prevalence of flavoured tobacco product use was highest among youth, followed by YA and adult 25+ any tobacco users. Within each age group, flavoured use was greatest among hookah, e-cigarette and snus users. Overall, menthol/mint, fruit and candy/sweet were the most prevalent flavour types at first and past 30-day use across age groups. For past 30-day use, all flavour types except menthol/mint exhibited an inverse age gradient, with more prevalent use among youth and YAs, followed by adults 25+. Prevalence of menthol/mint use was high (over 50% youth, YAs; 76% adults 25+) and exhibited a positive age gradient overall, though the reverse for cigarettes. Brand-categorised and self-reported flavour use measures among adults 18+ were moderately to substantially concordant across most products. Conclusions: Common flavours like menthol/mint, fruit and candy/sweet enhance appeal to young tobacco users. Information on flavour types used by product and age can inform tobacco flavour regulations to addess flavour appeal especially among youth.